The effect of hail protection nets on Glomerella leaf spot in 'royal Gala' apple - Goncalves M.J.* (2012)
In commercial apple orchards in southern Brazil, it is common to avoid hail damage by covering the trees with nets. This study was carried out to assess the effects of both black and white hail netting on the temporal dynamics of Glomerella Leaf Spot disease (GLS) in a commercial 'Royal Gala' apple orchard in a high-altitude region of southern Brazil during two growing seasons (2003/2004 and 2004/2005). Apple trees on M9 rootstock, trained to a slender spindle and with a spacing of 5.5 m × 3 m, were left uncovered (control) or covered with black or white hail netting. The incidence and severity of GLS were quantified biweekly from October to February by evaluating 100 leaves distributed randomly on four medium-height branches per plant on each 12 replications per treatment. Disease progress curves were constructed from the data and the epidemics were compared by using four epidemiological measures: the beginning of symptom appearance (BSA), the time to reach the maximum disease intensity (TRMDI), the maximum value of disease severity (Ymax), and the area under the disease progress curve (AUDPC). The highest intensity of GLS was observed in the plants under the black hail netting. Significant reductions in BSA and TRMDI and significant increases in Ymax and AUDPC were found among treatments in both growing seasons. However, no significant differences of GLS were found between the white hail netting and the control in either growing season. © 2011 Elsevier Ltd.